Similarities between Cognitive Models of Language Production and Everyday Functioning: Implications for Development of Interventions for Functional Difficulties. (14th June 2021) - Mis, Rachel; Giovannetti, Tania
Abstract: The loss of the ability to independently complete activities of daily living, such as meal preparation and household chores, is a defining characteristic of clinical dementia; however, minor difficulties in completing everyday activities emerge in the mild cognitive impairment stage, and even healthy older adults exhibit subtle functional difficulties compared to younger adults. These functional difficulties are associated with an array of negative outcomes, including decreased quality of life, higher costs of care, and increased frustration, depression, caregiver burden, and institutionalization. While cognitive models have been proposed to explain the functional deficits seen in dementia and subtler forms of cognitive decline, in contrast to other cognitive disorders such as aphasia, there are essentially no theoretically motivated interventions to address difficulties in everyday functioning. Proposed models of functional impairment share features with cognitive processing models of language, including hierarchical organization of representations and interactive, spreading activation; thus, an examination of aphasia interventions has the potential to inform the development of theoretically motivated interventions for everyday activities. This review first addresses the shared characteristics of cognitive models of everyday function and language, with a focus on linguistic production. Next, we will present aphasia interventions that target single‐word production, sentence production, short‐term memory, and semantics, and discuss their implications for everyday functioning interventions. We conclude with a discussion of limitations of the language‐everyday functioning comparison as well as areas of future research. Abstract : Mis and Giovannetti argue that theoretically motivated interventions for aphasia can serve as an instructive paradigm for the development of interventions to improve everyday functioning in older adults. They discuss existing aphasia interventions and hypothesized parallel targets in action based on shared characteristics between cognitive models of language and everyday action.